Development and Characterization of Triticum aestivum-Aegilops longissima 6Sl Recombinants Harboring a Novel Powdery Mildew Resistance Gene Pm6Sl - Tian, Xiubin; Chen, Qifan; Ma, Chao; Men, Wenqiang; Liu, Qianqian; Zhao, Yue; Qian, Jiajun; Fan, Ziwei; Miao, Jingnan; He, Jinqiu; Sehgal, Sunish K.; Li, Huanhuan; et al. (Frontiers in Plant Science, 2022)
Powdery mildew of wheat is a foliar disease with a worldwide distribution. Cultivation of resistant varieties is the most effective, economical, and environmentally friendly strategy to control this disease. Powdery mildew resistance genes (Pm) are the primary resources for resistance breeding, and new Pm genes are in constant demand. Previously we identified Aegilops longissima chromosome 6Sl#3 as a carrier of powdery mildew resistance, and designated the resistance gene as Pm6Sl. Here, we reported the design of 24 markers specific to 6Sl#3 on the basis of the full-length cDNA sequences of 6Sl#3 donor Ae. longissma acession TA1910, and the development of wheat-Ae. longissima 6Sl#3 introgression stocks by ph1b-induced homoeologous recombination. Further, 6Sl#3 introgression lines were identified and characterized by integration analysis of powdery mildew responses, in situ hybridization, and molecular markers, and Pm6Sl was mapped to a distal interval of 42.80 Mb between markers Ael58410 and Ael57699 in the long arm of 6Sl#3. Two resistant recombinants, R43 (T6BS.6BL-6Sl#3L) and T27 (Ti6AS.6AL-6Sl#3L-6AL), contained segments harboring Pm6Sl with less than 8% of 6Sl#3 genomic length, and two markers were diagnostic for Pm6Sl. This study broadened powdery mildew resistance gene resources for wheat improvement, and provided fundamental basis for fine mapping and cloning of Pm6Sl to further understand its molecular mechanism of disease resistance.